Dynamic nuclear polarization and overhauser shift on C60 - Radical anion salts - Dyakonov, Vladimir V.; Rösler, G.; Klos, Holger; Gotschy, Bernd; Denninger, G.; Hirsch, Andreas (Synthetic Metals, 1993)
Electronic and magnetic properties of C-tetraphenylphosphonium radical anion salts have been studied with the help of magnetic resonance technique. By applying the Overhauser shift method the Dynamic Nuclear Polarization, nuclear spin-lattice relaxation times and Overhauser shift have been determined simultaneously. The very short nuclear spin-lattice relaxation times of C and H are caused mainly by localized electronic moments rather than by the relaxation via conduction electrons. The C NMR signals from "bucky-balls" and phenyl groups of counterions can be separated. The results point to the incomplete charge transfer from the counterion to C molecule resulting in a large Overhauser shift signal from protons and carbon nuclei of the counterion. © 1993.